Generation of short and intense attosecond pulses - Khan, Sabih ud Din (Kansas State University, 2012)
Extremely broad bandwidth attosecond pulses (which can support 16as pulses) have been demonstrated in our lab based on spectral measurements, however, compensation of intrinsic chirp and their characterization has been a major bottleneck. In this work, we developed an attosecond streak camera using a multi-layer Mo/Si mirror (bandwidth can support ~100as pulses) and position sensitive time-of-flight detector, and the shortest measured pulse was 107.5as using DOG, which is close to the mirror bandwidth. We also developed a PCGPA based FROG-CRAB algorithm to characterize such short pulses, however, it uses the central momentum approximation and cannot be used for ultra-broad bandwidth pulses. To facilitate the characterization of such pulses, we developed PROOF using Fourier filtering and an evolutionary algorithm. We have demonstrated the characterization of pulses with a bandwidth corresponding to ~20as using synthetic data. We also for the first time demonstrated single attosecond pulses (SAP) generated using GDOG with a narrow gate width from a multi-cycle driving laser without CE-phase lock, which opens the possibility of scaling attosecond photon flux by extending the technique to peta-watt class lasers. Further, we generated intense attosecond pulse trains (APT) from laser ablated carbon plasmas and demonstrated ~9.5 times more intense pulses as compared to those from argon gas and for the first time demonstrated a broad continuum from a carbon plasma using DOG. Additionally, we demonstrated ~100 times enhancement in APT from gases by switching to 400 nm (blue) driving pulses instead of 800 nm (red) pulses. We measured the ellipticity dependence of high harmonics from blue pulses in argon, neon and helium, and developed a simple theoretical model to numerically calculate the ellipticity dependence with good agreement with experiments. Based on the ellipticity dependence, we proposed a new scheme of blue GDOG which we predict can be employed to extract intense SAP from an APT driven by blue laser pulses. We also demonstrated compression of long blue pulses into >240 µJ broad-bandwidth pulses using neon filled hollow core fiber, which is the highest reported pulse energy of short blue pulses. However, compression of phase using chirp mirrors is still a technical challenge.
Keywords: Attosecond; High harmonics; Optics (0752); Physics (0605)